Colonizing Palestine : the Zionist left and the making of the Palestinian Nakba - Ṣabbāgh-Khūrī, Arīj (Stanford, California : Stanford University Press, 2023)
"Among the most progressive of Zionist settlement movements, Hashomer Hatzair proclaimed a brotherly stance on Zionist-Palestinian relations. Until the tumultuous end of the British Mandate, movement settlers voiced support for a binational Jewish-Arab state and officially opposed mass displacement of Palestinians. But, Hashomer Hatzair colonies were also active participants in the process that ultimately transformed large portions of Palestine into sovereign Jewish territory. Areej Sabbagh-Khoury investigates this ostensible dissonance, tracing how three colonies gained control of land and their engagement with Palestinian inhabitants on the edges of the Jezreel Valley/Marj Ibn 'Amer. Based on extensive empirical research in local colony and national archives, Colonizing Palestine offers a microhistory of frontier interactions between Zionist settlers and indigenous Palestinians within the British imperial field. Even as left-wing kibbutzim of Hashomer Hatzair helped lay the groundwork for settler colonial Jewish sovereignty, its settlers did not conceal the prior existence of the Palestinian villages and their displacement, which became the subject of enduring debate in the kibbutzim. Juxtaposing history and memory, examining events in their actual time and as they were later remembered, Sabbagh-Khoury demonstrates that the dispossession and replacement of the Palestinians in 1948 was not a singular catastrophe, but rather a protracted process instituted over decades. Colonizing Palestine traces social and political mechanisms by which forms of hierarchy, violence, and supremacy that endure into the present were gradually created"--
People, land, and property : the process of settler colonization in Bilad al-Ruha -- Colonization by purchase : possession, expulsion, and replacement -- Encounters on the settler colonial frontier : kibbutz relations with their neighboring Palestinian villages -- From purchase to warfare : relations between kibbutz settlers and neighboring Palestinians during the "1948 events" -- Settler colonial memory : between recognizing and disavowing -- Representations of 1948 : from official representation to controversial memory.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 27, 2023).
eBooks on EBSCOhost
Keywords: Settler colonialism -- Palestine -- History -- 20th century; Kibbutzim -- Political aspects -- History -- 20th century; Labor Zionism -- Palestine -- History -- 20th century; Jewish-Arab relations -- History -- 1917-1948.; Palestinian Nakba, 1947-1948.; Collective memory -- Palestine; Palestine -- History -- 1929-1948.; Colonialisme de peuplement -- Palestine -- Histoire -- 20e siècle.; Kibboutz -- Aspect politique -- Histoire -- 20e siècle.; Sionisme socialiste -- Palestine -- Histoire -- 20e siècle.; Relations judéo-arabes -- Histoire -- 1917-1948.; Mémoire collective -- Palestine; Palestine -- Histoire -- 1929-1948.; HISTORY / Middle East / Israel & Palestine; Collective memory; Jewish-Arab relations; Kibbutzim -- Political aspects; Labor Zionism; Settler colonialism; Middle East -- Palestine; 1900-1999; History